Outdoor schools: Limits and dilemmas - Irena Smetáčková (Czech Pedagogical Society, 2011)
Outdoor school is a stable element of Czech educational system. However,many changes have occurred during the last twenty years in the purposes of outdoorschools and in their organization. The article presents various school statistics andresults of research which included questionnaire survey in elementary schools in Pragueand a case study of two classes. The study found that the outdoor school programmesare getting shorter, budgets for outdoor schools are reduced, and prices of outdoorschool programmes for parents are increasing. Because of high prices, almost 20 % ofpupils cannot attend outdoor schools. Nevertheless, according to teachers, pupils andparents, the main purpose of outdoor school programmes is to create a better socialclimate in peer groups. Because of high rates of absence, this goal is partly invalid.Another purpose should be that teachers and children get to know each other better.This goal is invalid as well because many schools hire commercial agencies which limitsthe time that pupils and teachers spend together.